Evaluation of functional outcome after osteosynthesis of intra articular distal humerus fracture with pre contoured locking compression plates - Mohammed, Faisal S.; Ingale, Akshay B. (International Journal of Research in Orthopaedics, 2020)
Background: Intra articular distal humerus fractures are challenging and cumbersome to treat. Therefore osteosynthesis of such fractures is required. The aim of our study was to evaluate the functional outcome of intra articular distal humerus fractures AO type 13C by osteosynthesis using olecranon osteotomy with pre contoured locking compression plates in orthogonal plate configuration. Methods: Thirty patients were included in our study comprising of 18 males and 12 females. Mean age was 39.63 years with mean follow up of 34 weeks. 7 were AO type 13C1, 9 were AO type 13C2 and 14 were AO type 13C3. Osteosynthesis was done for all fractures by olecranon osteotomy approach. Functional outcome was assessed using mayo elbow performance score. Results: Mean flexion attained at the end of follow up was 127.56 degrees with mean extensor lag of 7.16 degrees. Mean arc of motion was 120.4 degrees. Mean mayo elbow performance score at the end of follow up was 80.36. Mayo elbow performance score in patients aged less than 40 years of age was not statistically significant as compared to patients more than 40 years of age. Functional outcome was also dependent on fracture subtype. Conclusions: Osteosynthesis of distal humerus fractures AO type 13C using pre contoured locking compression plates in orthogonal plate configuration by olecranon osteotomy provides excellent visualization of fracture and better functional outcome.